The ILT family of leukocyte receptors. - Allan, D; Mcmichael, A; Braud, V (2000)
In this short review we examine the recently identified immunoglobulin-like transcript (ILT) family of receptors (also known as LIR and MIR). ILT are expressed by many leukocyte subsets, especially monocytic cells. Expression levels of certain ILT molecules allow definition of blood monocyte and dendritic cell (DC) subsets. Two receptors, ILT2 and ILT4, recognise a broad range of MHC class I molecules and transduce an inhibitory signal. Such recognition may give many cell lineages the potential to recognise and respond to MHC class I down-regulation.